Peripheral odontogenic fibroma with clear cell odontogenic epithelium. - Siar, C.H.; Ng, K.H. (1995)
The clinical and histological features of the peripheral odontogenic fibroma are briefly outlined. A case arising from the attached lingual gingiva between the mandibular right permanent first molar and the second molar in a 67 year old Indian female is reported here. The unusual occurrence of marked clear cell differentiation within the odontogenic epithelial component, and histogenetic link to the clear cell rests of the dental lamina and surface epithelium are discussed.